TINJAUAN DAN PERENCANAAN PLTA KEDUNGOMBO PURWODADI – JAWA TENGAH - Arika Iranawati; Dwi Putri Wulandari; Joetata Hadihardaja; Sri Sangkawati (Jurnal Karya Teknik Sipil, 2013)
Kedungombo Dam besides enabled for the fulfillment of the irrigation demands and raw water is also used for power plant. Kedungombo Hydro Electric Power Plant Kedungombo planned with the maximum discharge 61.8 m3/sec and  minimum discharge 45.00 m3/sec. Power designed by 22.50 MW. However, in reality the power generated is less than the designed power. The volume of the sediment in Kedungombo Dam to 2012 amounted to 34.47 million m3 and has reached the elevation of 56.80 m. While intakes are mounted at an elevation of 55.60 m, so the elevation of the intake should be increased. In addition, to increase the production of electricity, the power house was moved to a lower elevation. Design discharge for hydropower obtained from the discharge evaluation by using mass curve inflow over the last 5 years (from 2007 until 2012) obtained  design discharge of 34.77 m3/sec. Discharge release for 5 years (from  2007 until 2012) obtained an average discharge of 33.91 m3/sec, maximum discharge 61.8 m3/sec, and the minimum discharge of 49.02 m3/sec. When reviewing the irrigation  demands and raw water,Kedungombo Dam  must meet the requirements of 1,530.70 million m3 of water and discharge must flow with minimum 55.00 m3/sec. Kedungombo Hydro Electric Power Plant designed with the maximum discharge 61.80 m3/sec and minimum discharge 45.00 m3/sec, so the development of hydropower has taken maximum design discharge of 61.80 m3/sec. Hydro electric power plant structure that designed for operational support in order to function properly such as intake, penstock, control gate, turbines, tail race, and the draft tube. Results of the detailed design, are (1) intake using a towe with diameter 3,8 m on elevation +60.00. (2) Penstock (steel pipe) with diameter 3.8 m and the total length 287 m connected with intake on elevation +60.00. (3) Nett Head 60.00 m. (4) The power generated 32.37 kW. (5) Control gate using Canal 500x250x10 profile. (6) Turbine type used is Franciss Turbine. (7)Tail race stone masonry type in trapezium shape with b = 5.5 m, h = 2.6 m. From calculations of  power plant operations, the results of  Kedungombo power plant production can be increased by 78.87% from the original production. Average production of the Kedungombo Hydro Electric Power Plant 16.81 MW to 29.57 MW. Cost of constuction Kedungombo Hydro Electric Power Plant is estimated Rp 38.958.723.000.- (Thirty Eight Billion Nine Hundred and Fifty Eight Million Seven Hundred Twenty Three Thousand Rupiahs) and durations for execution is 17 weeks.